Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

douglas12

  • 2 years ago

Solve the system by the method of substitution. y = 3x + 8 y = 2x + 7 A. (1, 9) B. (–1, 5) C. (1, 11) D. (11, 1)

  • This Question is Closed
  1. jim_thompson5910
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    y = 2x + 7 3x+8 = 2x + 7 ... replace y with 3x+8 (since y = 3x+8) 3x-2x = 7-8 x = ???

  2. douglas12
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    -1

  3. jim_thompson5910
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    if x = -1, then y = 3x + 8 y = 3*(-1) + 8 y = ??

  4. douglas12
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    5

  5. jim_thompson5910
    • 2 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    correct, so (x,y) = (-1, 5)

  6. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy